Valorization of fish by-products: Purification of bioactive peptides from codfish blood and sardine cooking wastewaters by membrane processing - Ghalamara, Soudabeh (2021)
SFRH/BD/149347/2019 UID/QUI/50006/2019 POCI-01 -145-FEDER-016403.